Pendidikan Karakter dalam Projek Penguatan Profil Pelajar Pancasila (P5) pada Mata Pelajaran Pendidikan Agama Islam - Sulistiawati, Vina Mulia; Ramdhani, Khalid; H. Mansyur, Masykur (Universitas Majalengka, 2025)
The research aims to gain an in-depth understanding of the character education of Projek Penguatan Profil Pelajar Pancasila (P5) in the Islamic Religious Education subject at SMP Negeri 51 Bekasi. This research utilizes a qualitative approach with field research methods. Data collection was carried out by interviewing relevant teachers and students and analyzing documentation related to the research. The results indicate that there are six dimensions of P5, consisting of: (1) Faith and Piety to God Almighty and Noble Character; (2) Mutual Cooperation; (3) Critical Thinking; (4) Creativity; (5) Independence; (6) Global Diversity. From these six dimensions, it can be concluded that Islamic Religious Education learning is not merely about instilling values of faith and piety to Allah SWT and noble character. More than that, Islamic Religious Education learning, particularly at SMP Negeri 51 Bekasi, has represented or proven that this learning can instill all aspects of the P5 dimensions. Therefore, it can be said that Islamic Religious Education learning, particularly at SMP Negeri 51 Bekasi, has been comprehensive in its implementation.